MEDICAL TRANSLATION IN CONTEMPORARY INTERCULTURAL PROFESSIONAL COMMUNICATION - E. V. Pivanova (Гуманитарные и юридические исследования)
The item offers a focus on the need for theoretical development of special medical translation studies, which would be based on a text-centered approach, also placing an emphasis on linguo-pragmatic features of medical texts in view of their theme and genre as well as various activities adopted by the translator acting as an intercultural professional go-between in the area of theoretical and practical medicine. The author introduces a contaminated classification for text genres that are applied to the contemporary medical discourse and that require special theoretical description and analysis being the subject for the translator's professional activity.